An overview of the NTFP sub-sector in Vietnam (Viện Khoa học Lâm nghiệp Việt Nam, 2002)
NTFPs have provided essential, supplementary, and luxury materials to human communities for probably as long as and forests have co-existed. But even to day NTFPs continue to play vitals roles in the livehoods of communities,...